2004
DOI: 10.1007/s00270-003-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of a Spontaneous Dissection of the Superior Mesenteric Artery: A New Therapeutic Approach?

Abstract: Spontaneous dissection of the superior mesenteric artery (SMA) is rare and has been reported only sporadically. Therapeutic options are either a surgical approach, which is the more frequently adopted, or a simple observation. We report a case of spontaneous dissection of the SMA with a review of the literature and present a new therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 23 publications
2
31
1
3
Order By: Relevance
“…Concerning treatment of spontaneous isolated SMA dissection, a relatively high proportion of patients requiring surgical intervention has been previously reported. 21 However, several recent reports have indicated a high success rate with conservative management alone, 7,11,22 and our study showed that conservative treatment was successful in 96.6% of patients. Failure of conservative management during the follow-up period has been reported in previous studies, 23-25 and surgical interventions were required 10 days to 1 year after diagnosis, because of symptom recurrence.…”
Section: Disclosuresmentioning
confidence: 57%
“…Concerning treatment of spontaneous isolated SMA dissection, a relatively high proportion of patients requiring surgical intervention has been previously reported. 21 However, several recent reports have indicated a high success rate with conservative management alone, 7,11,22 and our study showed that conservative treatment was successful in 96.6% of patients. Failure of conservative management during the follow-up period has been reported in previous studies, 23-25 and surgical interventions were required 10 days to 1 year after diagnosis, because of symptom recurrence.…”
Section: Disclosuresmentioning
confidence: 57%
“…Reviewing the literature, there have been eight reported cases of SMA dissection treated by stent placement [4,5,10,[16][17][18][19] and all of them were treated successfully (Table I). It is still not certain that when is the optimal timing to perform endovascular therapy for patients with isolated SMA dissection.…”
Section: Discussionmentioning
confidence: 98%
“…In a case reported by Sparks [7], the patient underwent surgery 11 months after the initial diagnosis of DSMA for recurrent abdominal pain with extension of the dissection and aneurysmal dilatation of the artery. Among 28 cases described since 1975 and treated conservatively, Froment [9] noted a failure rate of 38.5% increasing to 50% in symptomatic patients. These cases indicated that medical treatment required close clinical and radiological follow-up for at least 12 months [3,21].…”
Section: Commentmentioning
confidence: 96%
“…The false lumen may thrombose [17]. The natural history of DMSA is not predictable and the optimal treatment may involve conservative management with [18] or without [12] anticoagulation, surgery [4,8], or percutaneous stent placement [9,19,20]. However, DSMA is a hazardous condition which may worsen [4].…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation